(untitled) (Raparin Journal of Humanities (RJH), 2025)
This research discusses in a description method the Impact of public relations in social media marketing. The research aims to analyze the mutual effect between public relations and marketing strategies and how these relations contribute to enhancing promotion and the making of the value of the brand. The research also discusses the tools and steps that public relations offers to support marketing in this digital era with focusing on its effect on building general opinion and long term customers. Public relations has become a core variable in marketing success. Especially in the age of social media which witnesses a major shift in the methods of social interactions and the impact on general opinion? This research represents the effect of public relations on marketing in doing so also understanding the new dynamics which links effective marketing and the making of the mental image of the brands. Public relations depend on building transparent social channels that are effective between firms and its prospects. With the emergence of social media these channels became interactive stages with an immediate sense that allowed public relations to develop innovative strategies that serve marketing goals. Public relations are no longer limited to enhancing the firm’s image, instead it became a major partner in relaying marketing messages, targeting prospects, and managing reactions. Within this framework classical public relations interact with new digital ones to offer a new value for marketing. For instance, public relations can contribute to enhance interactions with the marketing content, building impactful stories about products and services, and increase brand awareness. It also contributes to increase the prospect’s trust which directly affects purchase decisions and achieve customer loyalty.